2008
DOI: 10.2105/ajph.2007.110163
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Discrimination and Health Among Filipinos in the United States

Abstract: Racial discrimination in the workplace was positively associated with poor health among Filipino Americans after we controlled for reports of everyday discrimination and general concerns about one's job. This finding shows the importance of considering the work setting as a source of discrimination and its effect on morbidity among racial minorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 56 publications
1
82
0
1
Order By: Relevance
“…1, 2 Prior studies primarily relied on global measures of discrimination, 2 and few assessed the effects of discrimination in particular settings, such as the workplace. 35 The workplace is among the most common settings where individuals report experiencing discrimination 6, 7 and could be particularly deleterious for health. Individuals who experience workplace discrimination report greater work-related stress, 8, 9 which could lead to poorer health outcomes through adoption of unhealthy stress coping mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 Prior studies primarily relied on global measures of discrimination, 2 and few assessed the effects of discrimination in particular settings, such as the workplace. 35 The workplace is among the most common settings where individuals report experiencing discrimination 6, 7 and could be particularly deleterious for health. Individuals who experience workplace discrimination report greater work-related stress, 8, 9 which could lead to poorer health outcomes through adoption of unhealthy stress coping mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many studies demonstrate that the reporting of racial discrimination in childhood or adulthood is associated with illness. 6,7 A few studies go further, perhaps by specifying discrimination in multiple contexts (e.g., everyday discrimination vs workplace discrimination) 8,9 or by examining the interaction between discrimination and other factors, such as social strains. 10 However, a more complex and potentially more realistic model of racial health inequities can consider how race and racism intersect throughout the life course.…”
mentioning
confidence: 99%
“…8 Historical, racialized events can provide natural experiments from which to study the differential effects of discrimination on health across generations.…”
mentioning
confidence: 99%
“…Hammond et al (2010) in a study of discrimination among 604 multi-ethnic hospital employees found that African Americans were more likely than other ethnic groups to report frequent and multiple types of discrimination exposure and they also indicated higher levels of depressive symptoms. Several other studies have also shown the negative effects of discrimination on its victims (Roberts et al, 2004;Bhui et al, 2005;De Castro et al, 2008).…”
Section: Workplace Bias and Discriminationmentioning
confidence: 92%